2013
DOI: 10.1111/apt.12544
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low HCV viraemia by repeated HCV RNA testing predicts treatment failure to triple therapy with telaprevir

Abstract: SUMMARY BackgroundEarly on-treatment virological response is one of the most important predictors for sustained virological response (SVR) to treatment of chronic hepatitis C virus (HCV) genotype 1 infection with triple therapy including HCV protease inhibitors (PI). Treatment duration (24 vs. 48 weeks) is based on HCV RNA results at weeks 4 and 12 of PI therapy when HCV RNA must be 'undetectable' to allow shorter therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 13 publications
6
23
1
Order By: Relevance
“…This discrepancy in eligibility for shorter treatment is explained by the probabilities of detection of HCV RNA at the LOD of HCV RNA assays. In another study, Maasoumy et al showed that rates of detectable and undetectable HCV RNA at week 4 of triple therapy showed considerable variation of approximately 30% just by measuring the same samples several times using different versions of the Roche Cobas AmpliPrep/Cobas HCV test and HPS assay (24). Braun et al also demonstrated different rates of detectability by replicate testing of WHO standards at low viral loads using HPS or ART (25).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy in eligibility for shorter treatment is explained by the probabilities of detection of HCV RNA at the LOD of HCV RNA assays. In another study, Maasoumy et al showed that rates of detectable and undetectable HCV RNA at week 4 of triple therapy showed considerable variation of approximately 30% just by measuring the same samples several times using different versions of the Roche Cobas AmpliPrep/Cobas HCV test and HPS assay (24). Braun et al also demonstrated different rates of detectability by replicate testing of WHO standards at low viral loads using HPS or ART (25).…”
Section: Discussionmentioning
confidence: 99%
“…We thank Heron and colleagues for their interest in our report 1,2 and agree that the cost-effectiveness of this therapy is called into question by the number of patients who are unable to complete treatment and successfully achieve sustained virological response. We are analysing the cost-effectiveness of this regimen using real-world data.…”
mentioning
confidence: 86%
“…Similarly, in one study that assessed on-treatment HCV RNA of patients undergoing telaprevir-based triple therapy, samples were tested in triplicate by the first and second version of CAP/CTM and with HPS/CTM. In samples that had undetectable HCV RNA according to one assay, retesting with the respective other assays resulted in detectable HCV RNA in 32-50% of cases [44].…”
Section: Lower Limit Of Quantification and Limit Of Detectionmentioning
confidence: 99%
“…Thus, eligibility for shortened therapy should be based on attainment of undetectable HCV RNA at week 4 only, whereas patients with detectable/not quantifiable (<25 IU/ml) HCV RNA should receive a full course of therapy [43]. However, the HPS/CTM assay that was used in these trials has been shown to be less sensitive compared to CAP/CTM and ART, which are mostly used in clinical routine [39,44,57]. Indeed, some data suggest that assay-specific RGT criteria may be required given the significant performance differences among HCV RNA assays.…”
Section: The Role Of Hcv Rna Quantification During Protease Inhibitormentioning
confidence: 99%